2006
DOI: 10.1143/jjap.45.247
|View full text |Cite
|
Sign up to set email alerts
|

Method for Detection of Separatrix Surface Using Differential Double Probe

Abstract: Fine zinc particles were produced in an argon gas atmosphere and in a helium gas atmosphere of 1.33 × 10 4 Pa without thermal convection. To investigate the initial process of crystal growth, particles deposited at various places and at different moments during evaporation were collected. The shape and size of the particles were observed using a scanning electron microscope. When the evaporation time increased, the mean size of the deposited particles decreased in the argon gas atmosphere, while it increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As for the plasma position, it had been demonstrated that the calculated results agree well with the visible camera and soft x-ray array within an accuracy of the measurement, ∼3 cm [7]. To investigate the separatrix position more precisely, a new method was developed to measure the separatrix position using the 2-step electrostatic probes as follows [15,16]. Two sets of double probes with different pin lengths (difference : 5 mm) are inserted in the plasma.…”
Section: Equilibrium Codementioning
confidence: 96%
“…As for the plasma position, it had been demonstrated that the calculated results agree well with the visible camera and soft x-ray array within an accuracy of the measurement, ∼3 cm [7]. To investigate the separatrix position more precisely, a new method was developed to measure the separatrix position using the 2-step electrostatic probes as follows [15,16]. Two sets of double probes with different pin lengths (difference : 5 mm) are inserted in the plasma.…”
Section: Equilibrium Codementioning
confidence: 96%
“…We perform the direct observation of magnetic surfaces using the differential double probe (DDP), which is the two double probe system with long and short probe tips to detect the separatrix position as shown in Fig. 4(f) [13]. We can detect this by observing the current increment of the DDP through the differential amplifier when the top of the DDP crosses the separatrix when plasma was jogged from the core plasma region to the scrape-off layer (SOL) [14].…”
Section: Electrostatic Probe For Measuring the Ion Temperature And Mamentioning
confidence: 99%
“…Several probe methods have been developed to measure the ion temperature in fusion plasmas. [1][2][3][4][5] In the edges of these plasmas, the ion temperature T i has been found to exceed the electron temperature T e in tokamaks such as DITE, 6) TEXTOR, 7) and JFT-2M. 8) In the plasmas with T i > T e , the effect of the presheath is small so the ions reach the probe with almost the thermal velocity.…”
mentioning
confidence: 99%